Tenacidade de fratura da interface adesiva cerâmica-compósito - Bello, Yuri Dal (2013)
The objective of this study was evaluate the apparent interfacial fracture toughness (KA) and microtensile bond strength (σ) of the ceramic/resin adhesion zone, testing the hypothesis that KA and σ are affected by the ceramic surface treatment. Sixteen blocks of feldspatic ceramic (MII- Vita Mark II), were surface-treated with hydrofluoric acid (HF), silane (S), silane + MDP (SM) or combinations. We used Panavia F 2.0 or RelyX U 100 resin cements were used for cementation with resin blocks. The ceramic-cement-resin blocks were cut to fabricate bar-shaped specimens, which were tested in tension (σ). For KA, the specimens were indented (9,8 N; 10 s) with a Vickers indenter in the adhesive interface and loaded to failure in tension. Values of σ and the critical crack size (c) were used to calculate KA (KA = Y σ c1/2). The σ values were statistically analyzed using two-way Anova, Tukey (α=0.05) and Weibull. One-way Anova and Tukey (α=0.05) were used for KA. The association of HF and silane produced the highest values of m. The results of σ and KA were influenced by the ceramic surface treatment